PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR MAHASISWA JURUSAN PENDIDIKAN ILMU PENGETAHUAN SOSIAL FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Bella Berliana; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of learning styles on student learning outcomes majoring in Social Sciences Education, Faculty of Teacher Training and Education, University of Riau. This study uses quantitative descriptive methods and the population in this study were all active student majoring in Social Sciences Education Faculty of Teacher Training and Education, University of Riau in 2012 until the year of the year 2018 totaling 976 students and the samples were obtained using proportional random sampling techniques 98 respondents. Data collection instruments are questionnaires, documentation and interviews. Data analysis techniques used were descriptive analysis, hypothesis testing, multiple linear regression analysis and the coefficient of determination with the help of SPSS version 16.0. The results of this study are the learning styles of the Department of Social Sciences Students of the Teaching and Education Faculty of Riau University, the most dominant is the auditory learning style, because the value of Beta Standardized Coefficient held by the auditorial learning style variable is greater than the other independent variables. While learning outcomes are in the form cumulative achievements values obtained by students of the Department of Social Sciences, Teaching and Education Faculty of Riau University are categorized as very high in the range between 3,50-4,00. Furthermore, from the influence of learning styles on learning outcomes obtained f count> f table thus Ho is rejected. Then it can be concluded that there is an influence of learning styles on student learning outcomes majoring in Social Sciences Education, Faculty of Teacher Training and Education, University of Riau. The contribution of learning styles to the learning outcomes of students majoring in Social Sciences Education in the Teaching and Education Faculty of Riau University is 40.7%. The rest is influenced by other variables not examined.Key Words: Influence, Learning Style, Learning Outcomes